هه‌ڵسه‌نگاندنی شێوازه‌كانی دابه‌شبوونی وێستگه‌كانی سوته‌مه‌نی له‌ شاری كۆیه‌ به‌ بەكارهێنانی سیسته‌می زانیارییه‌ جوگرافییه‌كان (GIS) (لێكۆڵینه‌وه‌یه‌ك له‌ جوگرافیای شار) - سعيد, پ.د كامران طاهر; كریم, م. رۆژان كامران; رسوڵ, م.ی ژیار خدر (Sulaimani Journal for Humanities, 2023)
public services, specifically transportation services and transportation fuel stations are the most important factors that reflect the development of society and the level of livelihood of the population. Regarding the study area, there are 23 gas stations with a total area of 37,400 m2, which accounts for 16.0% of the total city area. Several criteria are used here for geographical distribution such as population, neighborhood area, urban belt, internal and external city roads and the distance and proximity to other services. About the Population, one station is for (4143) people. Those neighborhoods with high population density have few stations, and most of the stations are located in the eastern belt. Concerning the distribution of the stations are different since the direction of distribution is oval from east to west, it is circular in distance and contains 16 stations from north to south. According to the central criteria, the location for the stations is Haji Qadir neighborhood. due to the criterion of closest neighborly relationship, they are irregularly divided. According to the expert zone criteria, it extends from Koya-Sulaimani to Koya-Erbil. According to the affected area criteria, 61% of the stations are located in the affected areas, so there is a great imbalance in the distribution of fuel stations.
Keywords: Transporation; urban planning; services; city center and gas station